2022
DOI: 10.1093/g3journal/jkac066
|View full text |Cite
|
Sign up to set email alerts
|

Dual targeting of Saccharomyces cerevisiae Pso2 to mitochondria and the nucleus, and its functional relevance in the repair of DNA interstrand crosslinks

Abstract: Repair of DNA interstrand crosslinks involves a functional interplay among different DNA surveillance and repair pathways. Previous work has shown that interstrand crosslink-inducing agents cause damage to Saccharomyces cerevisiae nuclear and mitochondrial DNA, and its pso2/snm1 mutants exhibit a petite phenotype followed by loss of mitochondrial DNA integrity and copy number. Complex as it is, the cause and underlying molecular mechanisms remains elusive. Here, by combining a wide range of approaches with in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 85 publications
1
10
0
Order By: Relevance
“…To test this idea, Pso2 ∆ cells expressing MTS::mCherry with either the WT Pso2::GFP or Pso2 K97R,K575R ::GFP variant were grown in the absence or presence of 0.3% MMS. Consistent with previous work (Somashekara & Muniyappa, 2022), mCherry fused to the MTS localized exclusively to the mitochondria. As expected, we observed that the WT Pso2::GFP and Pso2 K97R,K575R ::GFP variant colocalized with DAPI‐stained nuclei in both untreated and MMS‐treated cells.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…To test this idea, Pso2 ∆ cells expressing MTS::mCherry with either the WT Pso2::GFP or Pso2 K97R,K575R ::GFP variant were grown in the absence or presence of 0.3% MMS. Consistent with previous work (Somashekara & Muniyappa, 2022), mCherry fused to the MTS localized exclusively to the mitochondria. As expected, we observed that the WT Pso2::GFP and Pso2 K97R,K575R ::GFP variant colocalized with DAPI‐stained nuclei in both untreated and MMS‐treated cells.…”
Section: Resultssupporting
confidence: 92%
“…As a first step to addressing these open questions, we constructed a plasmid (p416‐ Pso2 ::FLAG), in which the Pso2 gene was fused to one copy of the FLAG coding sequence to the C‐terminus. Our prior work demonstrated that ectopic expression of Pso2::1xFLAG protected Pso2Δ cells from cisplatin‐induced cell death and that its subcellular localization was similar to the wild type (WT) (Somashekara & Muniyappa, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations